Psychiatric presentation in undiagnosed intracranial space-occupying lesions: A case series - Daisy Rure; Nisha Kaithwas; Suneel S Kushwah; Nimisha Mishra; Dheerendra Mishra; Makhan Shakya (Industrial Psychiatry Journal, 2023)
Intracranial space-occupying lesions (SOLs) account for about 5–10 deaths per 100,000 in India. They present with physical symptoms such as headache, nausea, vomiting, and weakness; neurological symptoms such as seizures, and focal neurological deficit; and behavioral changes manifesting as depression (15–20%), anxiety (30–50%), psychosis (<5%), and personality changes (16–76%). Therefore, it is necessary to do an appropriate general, neurological, and behavioral examination for proper diagnosis and management. A series of four cases who reported to psychiatric outpatient with behavioural complaints and no focal neurological deficits were reported. The most common presentation of SOLs is seizure, headache, vomiting, and loss of consciousness. Along with this complaint, some patients may present with abnormal behavior. However, it is very rare for a SOL to present solely with psychiatric or behavioral complaints. Therefore, it becomes imperative to keep a close watch on the symptoms and send for timely investigations.